AWAKENING THE CARTESIAN DREAMER : Universal Values in Solidarity with an Evolutionary Universe - Orla O’Reilly Hazra (Journal of Dharma, 2012)
Humanity is part of a vast evolving universe. Earth our home, is alive with a unique community of life...The resilience of the community of life and the well-being of humanity depend upon preserving a healthy biosphere with all its ecological systems...The protection of Earth’s vitality, diversity, and beauty is a sacred trust...To realize these aspirations we must decide to live with a sense of universal responsibility, identifying ourselves with the whole Earth community as well as our local communities...The spirit of human solidarity and kinship with all life is strengthened when we live with reverence for the mystery of being, gratitude for the gift of life, and humility regarding the human place in nature.